High-Yield and Selective Photoelectrocatalytic Reduction of CO2 to Formate by Metallic Copper Decorated Co3O4 Nanotube Arrays - Shen, Qi; Chen, Zuofeng; Huang, Xiaofeng; Liu, Meichuan; Zhao, Guohua (Environmental science & technology, 2015)
Carbon dioxide (CO2) reduction to useful chemicals is of great significance to global climate and energy supply. In this study, CO2 has been photoelectrocatalytically reduced to formate at metallic Cu nanoparticles (Cu NPs) decorated Co3O4 nanotube arrays (NTs) with high yield and high selectivity of nearly 100%. Noticeably, up to 6.75 mmol·L–1·cm–2 of formate was produced in an 8 h photoelectrochemical process, representing one of the highest yields among those in the literature. The results of scanning electron microscopy, transmission electron microscopy and photoelectrochemical characterization demonstrated that the enhanced production of formate was attributable to the self-supported Co3O4 NTs/Co structure and the interface band structure of Co3O4 NTs and metallic Cu NPs. Furthermore, a possible two-electron reduction mechanism on the selective PEC CO2 reduction to formate at the Cu–Co3O4 NTs was explored. The first electron reduction intermediate, CO2 ads •–, was adsorbed on Cu in the form of Cu–O. With the carbon atom suspended in solution, CO2 ads •– is readily protonated to form the HCOO– radical. And HCOO– as a product rapidly desorbs from the copper surface with a second electron transfer to the adsorbed species.